2003
DOI: 10.1046/j.1442-2050.2003.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Salvage or planned esophagectomy after chemoradiation therapy for locally advanced esophageal cancer – a review

Abstract: Definitive chemoradiation (without esophagectomy) and neoadjuvant chemoradiation followed by planned esophagectomy are commonly used treatments for locally advanced esophageal cancer. These two treatment strategies have similar survival outcomes, so the value of planned esophagectomy is debated. However, persistence or recurrence of local disease is not uncommon after definitive chemoradiation. Salvage esophagectomy for isolated local failures of definitive chemoradiation is an option for selected patients. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 64 publications
(176 reference statements)
2
38
0
1
Order By: Relevance
“…Surgery to remove thoracic esophageal cancer is one of the most stressful therapeutic modalities and the development of chemotherapy and radiotherapy has occasionally shown an equivalent clinical benefit. Thus, the surgical indication for esophageal cancer has recently been discussed more seriously with respect to its survival benefit [11,12]. There have been many studies concerning esophageal cancers after gastrectomy, which revealed some differences in the clinicopathological features in comparison with esophageal cancer without a history of gastrectomy, such as for sex [13], tumor location [2,5,13], and multiple cancers [14].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery to remove thoracic esophageal cancer is one of the most stressful therapeutic modalities and the development of chemotherapy and radiotherapy has occasionally shown an equivalent clinical benefit. Thus, the surgical indication for esophageal cancer has recently been discussed more seriously with respect to its survival benefit [11,12]. There have been many studies concerning esophageal cancers after gastrectomy, which revealed some differences in the clinicopathological features in comparison with esophageal cancer without a history of gastrectomy, such as for sex [13], tumor location [2,5,13], and multiple cancers [14].…”
Section: Introductionmentioning
confidence: 99%
“…However it is well known that the morbidity of the rescue esophagectomy is higher when compared to the conventional esophagectomy after neoadjuvant therapy 20,24,30 . Some series have demonstrated greater tissue injury in patients undergoing the rescue esophagectomy, since the total dose used in the initial curative chemoradiation is higher (50 to 60 Gray), compared to 30 to 40 Gray used in the group of patients who try neoadjuvant therapy 24,28,30 . It is also relevant the fact that the conventional planned esophagectomy has lesser time interval between completion of chemoradiation and surgery, usually 20 to 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…The rescue esophagectomy has currently been disclosed once the exclusive chemoradiation presents an inherent failure of up to 60% with median survival of 12 to 18 months and a five-year survival rate of 10 to 30% 5,13,15,23,24,30,33 . However it is well known that the morbidity of the rescue esophagectomy is higher when compared to the conventional esophagectomy after neoadjuvant therapy 20,24,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, o controle locorregional é pobre com taxas de recidiva local relatada na literatura de 40-60%. A esofagectomia de resgate fornece a única possibilidade de cura para pacientes selecionados com recorrência tumoral ou persistência de doença após a quimiorradioterapia exclusiva, com taxas de sobrevida em cinco anos de aproximadamente 25% 10 . Do ponto de vista teórico, a cirurgia de resgate é dotada de maior dificuldade técnica e morbimortalidade operatória, devido à alta dose de radiação aplicada no leito tumoral e ao maior intervalo de tempo entre o término do tratamento Vol.…”
Section: Introductionunclassified